A Marketing Approach to the Study of Megacity: Necessity, Principles and Prospects - Rozhkov, Kirill (Journal of Economic Sociology, 2015)
This paper focuses on the feasibility of urban development concepts in the frame of different and contradictory needs of city residents. The aim of this paper is to justify the need for a marketing approach to big city investigations, to define its key principles, and show its main prospects. The author’s reasoning is based on the comparison of purposeful and spontaneous logics of city development. Through the analysis of various urban conflicts, the author shows that a spontaneous logic can prevent urban development concepts, projects, and separate decisions influencing residential life from being implemented when the diversity of residential needs is ignored. On the contrary, a marketing approach to urban studies could combine purposeful and spontaneous logic and, thereby, support city management. However, far too little attention has been paid in the previous resident-oriented marketing studies to the behavioural differences of user groups and the interrelated issue of simultaneous place use. There is also a critical gap in the topic of the selection process of target groups of the megacity and marketing to various groups with contradictory interests. Elements influencing strategic statement for a megacity are considered and, on this basis, the following basic principles of megacity marketing analysis are formulated: (1) to make a comparison between the city benefits sought by its residents and visitors, on one hand, and those which the city or urban concept offers, on the other; (2) to identify user groups with alternative requirements to the city and alternative urban product concepts; (3) to pay more attention to the way in which urban residents “use” the city when segmenting residents for marketing analysis. Techniques of megacity marketing analysis are demonstrated using the results of an empirical study of several Moscow districts. Results obtained from this research also have pragmatic value in that they can be used as an assessment tool for the feasibility of future urban development concepts.